الاستشهاد بالحديث النبوي عند مدرسة التقليبات الصوتية: معجم العين نموذجا: دراسة تحليلية - فرج، عبدالسلام يونس; الشرقاوي، محمد شحاتة عبدالحميد (جامعة المدينة العالمية, 2020)
هذه دراسة تحليلية في معجم العين للخليل بن أحمد الفراهيدي، أحد معاجم مدرسة التقليبات الصوتية، وقد اختار الباحث الاستشهاد بالحديث النبوي، ليكون موضوع الدراسة في هذا المعجم؛ للرغبة في دراسة حديث رسول الله -صلى الله عليه وسلم- والتعرف على شيء من فصاحته، والإعجاب بالخليل بن أحمد ومعجمه، ومحاولة التعرف على كيفية تناوله للشواهد الحديثية؛ لذا كان عنوان الدراسة هو: الاستشهاد بالحديث النبوي عند مدرسة التقليبات الصوتية (معجم العين نموذجا). وكان المحور الرئيس الذي يدور حوله هذا البحث هو: مدى أهمية وجود الشواهد الحديثية في معجم العين. وتشتمل الدراسة على مبحثين: المبحث الأول؛ موقف العلماء من الاستشهاد بالحديث، وقد قسم إلى مطلبين، هما: الاستشهاد بالحديث عند علماء النحو، والاستشهاد بالحديث عند علماء اللغة. والمبحث الثاني؛ توظيف الخليل للأحاديث في معجم العين، وقد قسم إلى ثلاثة مطالب: أولها: التعريف بالخليل بن أحمد كرائد لمدرسة التقليبات الصوتية، والتعريف بمعجم العين كأحد معاجم هذه المدرسة. وثانيها: منهج الخليل في توظيف الأحاديث. وثالثها: تصنيف الشواهد الحديثية على اعتبارات مختلفة. وأنهي البحث بخاتمة أجملت فيها النتائج التي توصل إليها الباحث من خلال الدراسة، والله الموفق إلى الخير.
This is a research in the Al-Ain dictionary for Khalil bin Ahmed Al-Farahidi, one of the dictionaries of the School of Vocalizations, and the researcher chose to cite the hadith of the Prophet, to be the subject of the research in this dictionary, because of the desire to study the hadith of the Messenger of Allah - may Allah bless him and grant him peace - and identify something from his eloquence, and admire Hebron Bin Ahmed and his lexicon, and to try to identify how he dealt with the Hadith evidence, so the title of the research was: Citing the Prophetic Hadith at the School of Phonetic (Al Ain dictionary as an Example). The main focus of this research was: How important is the existence of modern evidence in Al Ain dictionary. The research includes two topics: The first topic; the position of the scholars regarding the martyrdom of the hadith, has been divided into two requirements, namely: the concept of the hadith and its types, and the position of the scholars on the martyrdom of the hadith. The second topic: The employment of Hebron for hadiths in the Al Ain dictionary, and it was divided into three demands: The first: the definition of Hebron bin Ahmed as a pioneer of the School of Vocalizations, and the definition of the Al Ain dictionary as one of the dictionaries of this school. The second: The Hebron method in employing hadiths. And third: Classification of recent evidence based on various considerations. The research was concluded with a conclusion in which the results of the researcher were summarized through the study, and God is the best of success.
Keywords: السنة النبوية -- الشواهد الحديثية -- اللغة العربية -- علم الأصوات -- المعاجم اللغوية -- الفراهيدي، الخليل بن أحمد بن عمرو، ت. 170 هـ